Implementasi Pemenuhan Perlindungan Hak Anak Sebagai Tersangka Pelaku Tindak Pidana Dalam Proses Penyidikan - Aminanda, Rayhan; Indawati, Yana (Universitas Semarang, 2025)
This research aims to analyze the implementation of fulfilling the protection of children's rights as suspects of criminal acts in the investigation process at the Jombang Police. The urgency of this research is to find out how to fulfill the protection of children's rights as criminal suspects in the investigation process at the Jombang police station. The research method used by the author is empirical juridical. The results of this research show that fulfilling the protection of children's rights as suspects in criminal acts in the investigation process at the Jombang Police is carried out in 4 (four) forms of rights fulfillment processes, namely, the investigation process is carried out in a family atmosphere, providing legal assistance to child suspects, placing children in rooms. especially children during detention, carry out diversion efforts against the child suspect. Keywords: Protection of Children's Rights, Suspects, Investigation.